Wandering peoples : colonialism, ethnic spaces, and ecological frontiers in northwestern Mexico, 1700-1850 - Radding Murrieta, Cynthia (Latin America otherwise., 1997)
"Balanced and thorough work on colonial and early-19th-century Sonora and Sinaloa combines historical and ethnohistorical methodologies, narratives, statistical data, and analysis of the changing relations among Indians, villagers, miners, missionaries, and the state. Describes and analyzes the changes in Indian communities. Discussion of the transition between colony and independent Mexico provides a vision of changes and continuities. Exceptionally wide collection of sources"--Handbook of Latin American Studies, v. 58.